The Combined Effect of Syzygium Polyanthum and Honey Decoction on Lowering Blood Pressure: A Pra Experimental Approach - Dwi Antara Nugraha; Paulus Subiyanto; Esa Roy Tama (An Idea Health Journal, 2026)
Background: As of 2026, hypertension, often referred to as the "silent killer," has reached unprecedented prevalence globally Methods: This pilot study utilized a pra-experimental pre-post-test design without a control group. Total sampling was employed, resulting in a sample size of 35 participants. The Wilcoxon Signed-Rank Test was used to assess the effects of a boiled bay leaf-honey mixture on blood pressure Result: The intervention significantly reduced mean systolic blood pressure from 151.49 mmHg to 144.83 mmHg (p=0.018). In contrast, the reduction in diastolic pressure (84.89 mmHg to 83.29 mmHg) was not statistically significant (p=0.158). Conclusion: The findings indicate that this intervention may benefit elderly patients or those with isolated systolic hypertension (ISH). By significantly lowering systolic pressure without inducing unstable diastolic fluctuations, this decoction may serve as a safe complementary therapy to reduce cardiac workload in geriatric populations.